2019
DOI: 10.11604/pamj.2019.32.58.16779
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo et phénomène de Koebner suite à des injections de plasma riche en plaquettes

Abstract: Le vitiligo est un trouble commun et acquis de la pigmentation cutanée caractérisé par une perte sélective et souvent continue de mélanocytes épidermiques. Nous rapportons le cas d'une patiente ayant développé un vitiligo de la face suite à des injections de plasma riche en plaquettes. Le diagnostic de phénomène de Koebner a été retenu pour expliquer la survenue de vitiligo sur les zones mêmes d'injection de plasma riche en plaquettes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, clinicians should be cautious when interpreting the results of these studies which used the combination of a superior mode of therapy with a minor intervention [220]. Furthermore, repeated injections at short intervals are a painful procedure and can induce koebnerization [221]. Further larger RCTs with longer follow-up are required to confirm these findings.…”
Section: Alternative Treatment Optionsmentioning
confidence: 99%
“…However, clinicians should be cautious when interpreting the results of these studies which used the combination of a superior mode of therapy with a minor intervention [220]. Furthermore, repeated injections at short intervals are a painful procedure and can induce koebnerization [221]. Further larger RCTs with longer follow-up are required to confirm these findings.…”
Section: Alternative Treatment Optionsmentioning
confidence: 99%
“…14 Ejjiyar et al reported the onset of Koebner's phenomenon in a female patient phototype IV with the onset of facial non-segmental vitiligo after the third injection of PRP, for aesthetic purposes. 17…”
Section: Resultsmentioning
confidence: 99%
“…Needle acupuncture [130] Radiotherapy [131][132][133][134][135] Cupping therapy [136,137] Hirudotherapy [138] Specific Immunotherapy [139] Pulsed dye laser [140] Laser hair removal [141,142] Platelet-rich plasma injection [143] Subcutaneous Methotrexate/ Insulin Injection [144][145][146] Purified protein derivative (PPD)/ Mantoux test [31,147,148] Ayurveda [149] Colostomy Bag [150] Hair transplantation/ skin grafting [151,152] Mohs micrographic surgery [111] Electrocardiogram electrode negative pressure suction [153] Secondary to other diseases…”
Section: Vaccination [129]mentioning
confidence: 99%